1976
DOI: 10.1111/j.1432-1033.1976.tb10354.x
|View full text |Cite
|
Sign up to set email alerts
|

The Role of the Physical State of Lipopolysaccharides in the Interaction with Complement

Abstract: Lipopolysaccharides interact with complement onIy when they are present in a state of high aggregation with a high apparent molecular weight. Lipopolysaccharides in uniform salt forms prepared by electrodialysis and neutralization with different bases exhibited distinct differences in their anticomplementary activity which correlated with differences in their sedimentation coefficients.Conversion of smooth (S) form lipopolysaccharides into the low-molecular-weight triethylamine form completely abolished their … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
21
0

Year Published

1980
1980
2005
2005

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 79 publications
(26 citation statements)
references
References 15 publications
5
21
0
Order By: Relevance
“…9 shows the influence of different proton concentrations (pH variation in the range 1.6- 11.8) on the monolayer isotherms of a lipopolysaccharide R595 preparation, clearly demonstrating a reduction in the limiting area/molecule when changing from a basic to an acidic pH with the molecules then being more tightly packed. Parallel to this, the transition from the expanded to the compressed liquid phase, analogously to the P++a transition of the bilayer system, takes place at steadily decreasing pressures corresponding to an increase in the transition temperatures (see [32]). At extremely basic pH values (10.1, 11.8) this transition does not take place at all, the monolayer stays in the expanded liquid phase up to very high pressures.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…9 shows the influence of different proton concentrations (pH variation in the range 1.6- 11.8) on the monolayer isotherms of a lipopolysaccharide R595 preparation, clearly demonstrating a reduction in the limiting area/molecule when changing from a basic to an acidic pH with the molecules then being more tightly packed. Parallel to this, the transition from the expanded to the compressed liquid phase, analogously to the P++a transition of the bilayer system, takes place at steadily decreasing pressures corresponding to an increase in the transition temperatures (see [32]). At extremely basic pH values (10.1, 11.8) this transition does not take place at all, the monolayer stays in the expanded liquid phase up to very high pressures.…”
Section: Resultsmentioning
confidence: 99%
“…Further evidence for the importance of the fluidity of the hydrophobic portion of lipopolysaccharide comes from the fact that it strongly depends on the kind of salt form, as can be seen in the Table. Galanos and Liideritz [32] investigated the anticomplementary activity of various lipopolysaccharides from Salmonella in different salt forms. The Na' salt form lipopolysaccharide gave the highest activity, decreasing in the sequence natural, ethanolamine, and triethylamine salt forms.…”
Section: Correlation Of Biological Effectsmentioning
confidence: 99%
“…tilled water and adjusted to pH 7.2 with triethylamine. The physicochemical and biological properties of the two LPSs were described elsewhere (14,16,18,32). '4C-labeled LPS of S. abortus-equi and S. Minnesota R595 were prepared from bacteria grown on ['4C]glucose-containing medium.…”
mentioning
confidence: 99%
“…The basis for such inherent variability in the capacity of various lipopolysaccharides to interact with complement is not completely understood and probably reflects both the chemical composition of the lipopolysaccharide as well as its physical state. With respect to the latter variable, Galanos and Liideritz [5] have clearly documented the importance of molecular weight in the anticomplement activity of a variety of lipopolysaccharide preparations. In these studies they demonstrated that the conversion of smooth (S) form lipopolysaccharides to their low molecular weight triethylamine salt form results in a marked reduction of anticomplement activity, while conversion to their respective high molecular weight salt form results in enhanced activity.…”
mentioning
confidence: 99%